Extent of N-terminus exposure of monomeric alpha-synuclein determines its aggregation propensity - Amberley D. Stephens (Nature Portfolio, 2020)
In Parkinson’s disease (PD) the monomeric protein alpha-synuclein (aSyn) misfolds and aggregates into insoluble fibrils. Here the authors use NMR measurements and hydrogen–deuterium exchange mass spectrometry and find that the more solvent exposed the N-terminus of aSyn is, the more aggregation prone its conformation becomes, and further show how PD mutations and post translational modifications influence the extent of the N-terminus solvent exposure.